Rescue Transsplenic Gastric Varices Embolization in a Patient of Massive Gastric Variceal Bleed Secondary to Complete Splanchnic Portal Venous System Thrombosis - Sahoo, Biswajit; Panigrahi, Manas Kumar; Nayak, Manoj Kumar; Sasmal, Prakash Kumar; Pitchaimuthu, Arunprakash (Journal of Clinical Interventional Radiology ISVIR, 2024)
Endoscopic sclerotherapy is the first-line modality to manage gastric variceal bleeding; however, knowledge of other treatment options is also essential, especially in case of failure of the endoscopic approach. We are reporting a rare case of successful rescue gastric varices embolization through the transsplenic route in a gastric varices bleeding patient who presented with massive hematemesis and blood from the ileostomy drain site secondary to complete splanchnic portal venous system thrombosis when all other treatment options were not feasible or unsafe. Proper cross-sectional imaging evaluation, knowledge of treatment options, and understanding of intraprocedural challenges are essential for managing gastric varices.
Keywords: gastric varices; embolization; gastrointestinal hemorrhage